The Determinants of Father Involvement and Connections to Children's Literacy and Language Outcomes: Review of the Literature. Issue 4 (18th May 2016) - Varghese, Cheryl; Wachen, John
Abstract : This review synthesizes findings from the literature about the impact of father involvement on children's literacy and language outcomes. Various proximal and distal factors influence levels of fathers' involvement in literacy activities and fathers' contributions to language development. Fathers' education, income level, residence status, and relationship with the child's mother were indirect factors associated with children's literacy and language outcomes. Fathers also made unique, direct contributions to their children's literacy and language outcomes through the use of complex language, engagement in reading and writing activities, and responsive parenting behaviors. This review concludes by identifying gaps in the literature about other important contextual factors that may influence father involvement and about specific types of literacy activities that fathers engage in with their children.